Magnetic ground state of FeSe - Qisi Wang (Nature Portfolio, 2016)
Different ground states of high-temperature superconductors reveal complex nature of magnetism. Here, Wang et al. report stripe and Néel spin fluctuations coexisting with non-magnetic nematic phase in FeSe, providing a viewpoint towards understanding the magnetism of cuprate and iron-based superconductors.